Nanocrystalline Ni5P4: a hydrogen evolution electrocatalyst of exceptional efficiency in both alkaline and acidic media. Issue 3 (28th January 2015) - Laursen, A. B.; Patraju, K. R.; Whitaker, M. J.; Retuerto, M.; Sarkar, T.; Yao, N.; Ramanujachary, K. V.; Greenblatt, M.; Dismukes, G. C.
Abstract : Crystalline Ni5 P4 evolves hydrogen with electrical-efficiency comparable to platinum—while being corrosion-resistant in both acid and base for >16 hours. Abstract : Producing hydrogen (H2 ) by splitting water with fossil-free electricity is considered a grand challenge for developing sustainable energy systems and a carbon dioxide free source of renewable H2 . Renewable H2 may be produced from water by electrolysis with either low efficiency alkaline electrolyzers that suffer 50–65% losses, or by more efficient acidic electrolyzers with rare platinum group metal catalysts (Pt). Consequently, research has focused on developing alternative, cheap, and robust catalysts made from earth-abundant elements. Here, we show that crystalline Ni5 P4 evolves H2 with geometric electrical to chemical conversion efficiency on par with Pt in strong acid (33 mV dec −1 Tafel slope and −62 mV overpotential at −100 mA cm −2 in 1 M H2 SO4 ). The conductivity of Ni5 P4 microparticles is sufficient to allow fabrication of electrodes without conducting binders by pressing pellets. Significantly, no catalyst degradation is seen in short term studies at current densities of −10 mA cm −2, equivalent to ∼10% solar photoelectrical conversion efficiency. The realization of a noble metal-free catalyst performing on par with Pt in both strong acid and base offers a key step towards industrially relevant electrolyzers competing with conventional H2 sources.